1989
DOI: 10.1021/bi00445a004
|View full text |Cite
|
Sign up to set email alerts
|

Identification by proton nuclear magnetic resonance of the histidines in cytochrome b5 modified by diethyl pyrocarbonate

Abstract: Diethyl pyrocarbonate (DEP) is an electrophilic reagent that is used to modify reversibly the histidine residues of proteins. Unfortunately, the lability of the acylated histidine adduct usually does not permit the isolation and identification of the modified histidine. By use of 500-MHz proton NMR spectroscopy, it has been possible to identify the C-H resonances of the nonaxial histidines of trypsin-solubilized bovine, rabbit, and porcine cytochrome b5 and therefore observe the interaction of DEP with specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
3
24
1
Order By: Relevance
“…In particular, we note that the pKa of cytochrome b, residue His-26 that we have implicated above as undergoing a significant binding-induced pKa shift is also predicted to be acutely sensitive to ionic strength (Mauk et al, 1986;Altman et al, 1989).…”
Section: Northrup Personal Communication)mentioning
confidence: 94%
“…In particular, we note that the pKa of cytochrome b, residue His-26 that we have implicated above as undergoing a significant binding-induced pKa shift is also predicted to be acutely sensitive to ionic strength (Mauk et al, 1986;Altman et al, 1989).…”
Section: Northrup Personal Communication)mentioning
confidence: 94%
“…Figure 9 shows two distinct patterns that are possible for the fully H-bonded Glu11-His15-Ser20 triad. NMR studies have shown that His15 has a pK a of $8.5 in bMc holo-b 5 (Altman et al, 1989), as well as in rat Mc holo-and apo-b 5 (Moore et al, 1991). It is therefore safe to assume that His15 in bMc apo-b 5 also has a pK a of $8.5, and is protonated at the pH of 7.0 utilized in our studies (as in Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Irrespective of whether P-450 2B4 was labelled to the extent of a statistical average of 3.5 or 11.2 carbethoxy groups introduced per polypeptide within the time frame of the experiment, biphasic kinetic patterns were observed ( Figures 1B and 1C). Unless the particular pK a values for the individual histidines or specificities in solvent accessibility accounted for this dualism, the slowreacting species might have participated in hydrogen bonding with proton donors [34] ; as is well known, the electrophilic DEPC molecule interferes preferentially with the unprotonated form of histidine [24]. From the tracings depicted in Figure 1(C), the proportions of fast-and slow-reacting material were computed as 35 and 65 % respectively, characterized by pseudo-firstorder rate constants of 0.3 s −" and 0.06 s −" .…”
Section: Characteristics Of P-450 2b4 Modification By Depcmentioning
confidence: 99%